Evaluation of quality indicators contacting the surface of the tribological system «Wheel – Rail» - Kulichenko, A. J.; Kuzin, N. O.; Vakulenko, I. O. (Science and Transport Progress, 2013)
Purpose. Modern ideas about the contact interaction of bodies in friction are based on models that take into account the geometric parameters of the surface layers constituting tribosystems. These models provide a high level of adequacy to describe the features of the relief of the surfaces of parts and their impact on the performance characteristics of friction in the elastic stresses. However, the possibility of plastic deformations in the surface layers, particularly before using friction systems, these models do not account for. The aim of this work is the development of new mathematical approaches previously applied accounting strains and their effect on the performance of tribosystems. Methodology. Using the contact mechanics approaches analyzed the influence of preload on contacting a flat rough surfaces using a model based on the assumption of normal distribution of heights and roughness of plastic deformation at the first load. Findings. Analytically determined that under moderate pressure reduction from baseline, the actual contact area is proportional to the pressure in the 2/3 power. Originality. It is found that the contact patch size is proportional to the pressure of the first load. Practical value. It is established that at pressures lower than originally applied to the contact surfaces, the high values of the actual surface contact, the number of patches of actual contact are typical, than for the same pressure at the first load.